ANALISIS PENPAPATAN DAN KELAYAKAN USAHA INDUSTRI TAHU “DANI” DI KOTA PALU - Muhammad Suhdi (Universitas Tadulako, 2015)
This research aimed to determine the level of income and feasibility of tofu Daniindustrial enterprises at Miangas street of SouthPalu. This research was conducted from July to September 2014. The research object was determined purposively. Primary and secondary data were analyzed using income and feasibility analysis of revenue cost ratio. The result of this research shows that the average income received by the tofu industry was IDR3,321,714 for each month. By using R/C formula, it is obtained R/C=1.18 indicating that the tofu enterprises is feasible because R/C>1.Key words : Income, Tofu, worthiness.